Whey Biological Properties and Alternative Uses - Gigli, Isabel (IntechOpen, 2019)
Whey - Biological Properties and Alternative Uses proposes to rethink our use of agro-industrial by-products. Especially, those from cheese production, which although contain 50% of the nutrients of the original milk, are treated as waste. In this book, the authors offer alternative processes beyond the traditional ones, such as the production of vodka beverages from fermented whey, lactose-free isotonic beverages and glycomacropeptides in the food industry. Also, it discusses alternative uses of buttermilk: the production of biofilms, beverages, and microbiology additives. As always, the emphasis is on reducing environmental impact during food production and finding new strategies to reduce the waste of raw materials with nutritional value. This book is an excellent opportunity for graduate students and researchers from other areas to become aware of the problems faced when considering agro-industrial by-products with nutritional value as waste.